PTU-309 Assessing the impact of a specialist dietitian led weight management service in hepatology. (22nd June 2015) - Hyslop, L; Appleby, VJ; Roslan, H; Moreea, S
Abstract : Introduction: In 2013 Health service for England (HSE) reported that 62.1% of adults had a body mass index (BMI) of more than 25 kg/m 2 . Obesity is a risk factor for non-alcoholic fatty liver disease (NAFLD) which is the most common cause of liver disease in the United Kingdom and western countries. Reduction in total body weight (TBW) through diet and lifestyle modification is the mainstay of management for NAFLD. We aimed to assess the impact of an outpatient dietitian led specialist weight (wt) management (mgt) service offered exclusively to patients (pts) known to hepatology services on changes in wt observed. Secondary outcomes assessed included reasons for referral to the service, the demographics of pts, adherence to follow up (FU) through the service and whether any wt loss was maintained 6 months post discharge (d/c) from the service. Method: Information was analysed from a database created and maintained by dietitians. Data was collected on all pts accessing the service for 33 months between 2012–2014. Results: In 33 months, 72% (204/284) of pts referred to the service attended for assessment (axe) (144/204 (71%) males (M); 60/204 (29%) females (F); age range 16–19, median age 43). 116/204 (57%) of pts were Caucasian and 88/204 (43%) of Asian ethnicity. After axe, future FU was optional. FU ranged from 1–12 appointments (apt): 79/204 (39%) attended 1 FU, 39/204 (19%) attended 2 FU, 21/204 (10%) 3 FU, 28/204 (14%) 4 FU apt and 37/204 (18%) attended 5 or more apt. At the end of the study 19/204 (10%) were still receiving care, 60/204 (29%) of pts attended all arranged FU, 104/204 (51%) of pts were d/c due non-attendance; 15/204 (7%) self d/c, 6/204 (3%) were lost to FU. 113/204 (55%) had more than 1 FU apt and wt changes were recorded in this cohort. FU time ranged from 4–107 weeks. In total 88/113 (78%) lost weight (59M, 29F), of these 35/88 (40%) of pts lost more than 5% of their TBW. Wt loss ranged from 0.3–30.4 kg; average wt loss: 4.1 kg per pt. No pts in this cohort received wt mx surgery. Long term data was available for 33 pts 6/12 after d/c from the service; 16/33 (48%) had regained wt, 4/33 (12%) had remained stable (defined as less than 0.5 kg increase or decrease in wt) and 13/33 (40%) had continued to lose wt. Conclusion: Even though a significant number of patients failed to engage with service, wt loss results observed in pts adhering to FU and attending more than 1 apt with the dietitian led service were very encouraging. Poor engagement may be due to a lack of motivation, poor education on the role of the dietitian or pts failure to take ownership of their medical problems. Once d/c from the service, 48% of patients regained weight suggesting that motivation to continue to modify lifestyle and diet is poor once the period of active FU has ended. Disclosure of interest: None Declared.